INVESTIGATION OF THE CAUSES OF THE SLIDING ON THE 123KM ON THE KORINTHOS-TRIPOLIS NATIONAL ROAD AND WORKING TECHNIQUES TO RESTORE THE STABILITY - Μαρίνος Π.; Καββαδάς M.; Ντουνιάς Γ.; Προβιά Α. (Bulletin of the Geological Society of Greece, 2004)
The paper deals with the important landslide of a 220m width at the area of the 123km on the Korinthos-Tripolis national road as well as the remedial measures in order to restore the stability of the road. The sliding caused the traffic interruption on the national road at 08/02/2003 and for the next two months. The service was restored after the development of a bypass road on the same position with the sliding. The geomorphological features of the area indicate that there were sliding problems in the past which they became serious after the construction of the national road by the additional load of the embankment of the road and the increased infiltrations. The main remedial work was the toe buttress of the unstable slope by the construction of a 15m high fence in the valley and appropriate drainage on the foot of the sliding and at the same time it is re-arranged the riverbed through the development of a sewer along with the use of a drainage network.